Labiaplasty of bilateral labia minora hypertrophy with recurrent abscesses - Yan-Shijing Zhou; Dan Wu; Han-Dan Xiong; Yong-Le Ruan; Bo Duan (IMR Press, 2021)
Background: Labia minora hypertrophy is often overlooked in paraplegic women, here we present a rare case of bilateral labia minora hypertrophy with recurrent abscesses. A 31-year paraplegic woman presented with labia minora hypertrophy. The main patient complaints were the recurrent inflammation and swelling of the labia minora. Physical examination showed stage III labia minora hypertrophy with multiple cysts. Upon patient's agreement, edge resection of labia minora reduction was performed, and redundant labial tissue and cysts were resected completely. The patient was discharged for home care in good condition on postoperative day 7. Six-month post-operation telephone follow-up showed good recovery with no significant complications. In this case, long-term sitting together with diaper use might increase susceptibility to labia minora hypertrophy and labial abscesses, as a result of continuous mechanical irritation. Conclusions: We present this case to promote early awareness of such condition in paraplegic women and support early surgical treatment for patients suffering from labial abscesses.